Archeological Approaches in Jordan From 1800 Until Now - Al-Ghul, Omar A. (Jordan Journal for History and Archaeology, 2022)
Since the early nineteenth century, individuals interested in the antiquities of Jordan investigated, documented, and interpreted the archaeological finds they encountered or excavated in this country. Their approaches developed over time, not only due to the advancement of scientific methods and tools, but also because during the last two centuries major changes affected the religious and political motivations of western archaeology in the southern Levant. In the first part, the paper traces the basic elements of these developments and their intellectual background and, in a second part, it outlines the methods Jordanian archaeologists utilized to engage with their own cultural heritage over the same period. The paper concludes with recommendations for Jordanian archaeologists that would pave the way for a state-of-the-art investigation of Jordanian antiquities, on the one side, and for a proper appreciation of the contribution of Jordanian archaeology to the Jordanian cultural identity, on the other.